Propagation of Tau via Extracellular Vesicles - Pérez, Mar; Avila, Jesús; Hernández, Félix (Frontiers in Neuroscience, 2019)
Extracellular vesicles (EVs), like exosomes, play a critical role in physiological processes, including synaptic transmission and nerve regeneration. However, exosomes in particular can also contribute to the development of neurodegenerative conditions such as Alzheimer’s disease (AD), Parkinson’s disease, and prion diseases. All of these disorders are characterized by protein aggregation and deposition in specific regions of the brain. Several lines of evidence indicate that protein in exosomes is released from affected neurons and propagated along neuroanatomically connected regions of the brain, thus spreading the neurodegenerative disease. Also, different cell types contribute to the progression of tauopathy, such as microglia. Several groups have reported tau release via exosomes by cultured neurons or cells overexpressing human tau. Although the exact mechanisms underlying the propagation of protein aggregates are not fully understood, recent findings have implicated EVs in this process. The AD brain has two hallmarks, namely the presence of amyloid--containing plaques and neurofibrillary tangles, the latter formed by hyperphosphorylated tau protein. Both amyloid peptide and tau protein are present in specific exosomes. This review summarizes recent advances in our understanding of exosomes in the pathology of AD, with a special focus on tau protein.